A qualitative study about internationalization of Turkish textile & clothing industries - Divrik, Bahar; Baykal, Elif (Slovak University of Technology in Bratislava, 2022)
The national textile and clothing industries do not operate in isolation anymore; they are significant parts of one global sector which serve to the whole world. The Turkish textile and clothing industries are mainly export oriented and like other developing industries, they have an important role in the internationalization of the Turkish economy with their contribution to GDP, trade and employment. This article reviews the major developments that shaped the internationalization process of Turkish textile & clothing industries. Findings from semi-structured case studies with 14 Turkish textile and clothing industries tries to highlight the changes occurring currently in the industries. The qualitative data obtained from our research gives deep and detailed understanding of the Turkish textile and clothing industries.
Keywords: History of Turkish Textile Industry; Internationalization; Turkish Clothing Industry; Turkish Textile Industry; Qualitative Study